Method of Teaching Uzbek Language in Higher School in Paradigm Personally Oriented Education - Ruziyeva Sadokat Khasanovna (International Journal on Integrated Education, 2022)
The article discusses the content of the course "Methods of teaching the Uzbek language in higher education" in line with personality-oriented education. The main emphasis is on the system of tasks for individual independent work aimed at developing methodological concepts and applying knowledge in various conditions.